Efektivitas Pelatihan Kerja terhadap Kinerja Karyawan di PT BPR. Hayura Artalola - Rian Akbar Maulana; Alda Ramadhika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the effectiveness of job training in improving employee performance at PT. BPR Hayura Artalola. The background of the study is based on findings in the field that indicate that there is still a mismatch between training materials and their implementation in daily work. Although training has been carried out routinely every six months, some employees still have difficulty in carrying out their duties independently, which has an impact on the quality of service to customers. This study uses a qualitative approach with a descriptive method, through observation and interviews with employees and related parties. The results of the study indicate that job training is considered quite effective in improving employee knowledge and skills, especially in terms of service and administration. However, there are still obstacles in the application of training materials, such as the gap between theory and practice, and time constraints in mastering internal digital systems. This mismatch factor is also exacerbated by the inequality of understanding between employees, especially when the volume of work increases. Therefore, it is recommended that future job training be designed to be more varied and applicable, with methods such as simulations, case studies, group discussions, and mentoring programs to support understanding and application of materials more effectively in the field.